Where to stand? Researcher involvement in early education outdoor settings. Issue 2 (3rd April 2022) - Speldewinde, Christopher
ABSTRACT: Background: Prior to approaching any field site activity, the question of how researchers in education will interact with the participants in terms of positionality requires careful thought. Observation is often used by educators and researchers as a means of collecting informal data on children's development and learning in early childhood education and care (ECEC) classroom settings. As data collection often involves varying degrees of observation and participation, there is a need for a clear articulation of researcher involvement. When the classroom is an outdoor, nature-based setting, particular challenges can arise in this regard. Purpose: This small-scale study sought to explore these challenges in the context of early years of STEM teaching and learning. The research was situated within bush kindergartens (also known as 'bush kinders'), a developing context in Australian early childhood education. The open spaces of nature reserves, forests, beaches and paddocks all constitute settings for bush kinders. Method: The study employed an ethnographic lens to the teaching and play activities of around 10 educators and 120 four- to five-year-old children in four Australian bush kinders during 2015, 2017 and 2020. Much of the study was devoted to observation and participation in the activities that the children were undertaking. Influenced by a research tradition that places researcher participation and observation on a continuum of completeness, differences in researcher involvement that occur in nature-based education and care settings were categorised. Findings: It was determined from this categorisation that researcher involvement with participants ranged from low to high. The in-depth analysis allowed identification of how this range of involvement provides both benefits and limitations upon the researcher's involvement with teacher and child participants. Conclusions: This paper offers a contribution to the methodological discourse on ethnographic research in ECEC outdoor settings. In drawing close attention to the ways in which researcher involvement in the field may vary, it provides a framework of reference that could be helpful to other researchers engaged in designing and carrying out ECEC research in diverse outdoor settings.